2020
DOI: 10.1002/glia.23904
|View full text |Cite
|
Sign up to set email alerts
|

The delicate balance between neurotoxicity and neuroprotection in the context of HIV‐1 infection

Abstract: Human immunodeficiency virus type-1 (HIV-1) causes a spectrum of neurological impairments, termed HIV-associated neurocognitive disorder (HAND), following the infiltration of infected cells into the brain. Even though the implementation of antiretroviral therapy reduced the systemic viral load, the prevalence of HAND remains unchanged and infected patients develop persisting neurological disturbances affecting their quality of life. As a result, HAND have gained importance in basic and clinical researches, war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 277 publications
(363 reference statements)
0
7
0
Order By: Relevance
“…With regard to viral infections, glial cells can be primary targets of neurotropic viruses, such as the human immunodeficiency virus type 1 (HIV-1) and zika virus (ZIKV). Microglia and astrocytes constitute CNS reservoirs of HIV-1 [ 93 , 94 ], promoting neuroinflammation, which can explain neuronal damage and neurocognitive disorders in a number of patients, considering the relative incapacity of HIV-1 to directly infect neurons [ 95 ]. Due to the presence of AXL receptor, astrocytes and microglia are potentially the primary cells targeted by ZIKV in the CNS [ 96 ].…”
Section: Neurochemical Changes and Molecular Mechanisms Associated With Gliotoxicitymentioning
confidence: 99%
“…With regard to viral infections, glial cells can be primary targets of neurotropic viruses, such as the human immunodeficiency virus type 1 (HIV-1) and zika virus (ZIKV). Microglia and astrocytes constitute CNS reservoirs of HIV-1 [ 93 , 94 ], promoting neuroinflammation, which can explain neuronal damage and neurocognitive disorders in a number of patients, considering the relative incapacity of HIV-1 to directly infect neurons [ 95 ]. Due to the presence of AXL receptor, astrocytes and microglia are potentially the primary cells targeted by ZIKV in the CNS [ 96 ].…”
Section: Neurochemical Changes and Molecular Mechanisms Associated With Gliotoxicitymentioning
confidence: 99%
“…A previous study suggested that Cdk5 is a regulator of various neuronal cell death cascades (37). However, some studies have provided contradictory evidence indicating that Cdk5 provides neuroprotection in some conditions (38,39). Several studies have revealed that the influence of Cdk5 on cell death depended on its subcellular localization as opposed to its activity.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, transmigration of this macrophage population—which is highly susceptible to HIV infection—across the BBB into the CNS is critical to the pathogenesis of HAND. Work analyzing some of the mechanisms contributing to the entry of this mature monocyte subset into the brain has shown the presence of extremely increased sensitivity to CCL2 upon CC-chemokine receptor 2 (CCR2)-mediated HIV infection [ 54 , 55 ].…”
Section: The Entry Of Hiv-1 Into Microglial Cells and Their Susceptibility To The Virus Relevant Studies About The Mechanism Of Infectionmentioning
confidence: 99%
“…The HIV-1 Tat protein can activate the NLR and increase caspase-1 and IL-1β levels in microglia, which, in turn, generates TNF-α and IL-6 and intensifies the proinflammation response [ 16 ] ( Table 1 ). HIV-1 infection in microglial cells can also produce reactive oxygen species (ROS) and reactive nitrogen species (RNS), such as quinolinic acid, arachidonic acid, and nitric oxide [ 55 ]. Moreover, the presence of HIV-1 in the brain can cause the expression of inducible hypoxia factor (HIF)-1, leading to the generation of mitochondrial dysfunction and oxidative stress [ 52 , 74 ].…”
Section: The Entry Of Hiv-1 Into Microglial Cells and Their Susceptibility To The Virus Relevant Studies About The Mechanism Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation